1992
DOI: 10.1111/j.1460-9568.1992.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopic Localization of the Neutral Metalloendopeptidase EC 3.4.24.16 in the Mesencephalon of the Rat

Abstract: The topographic and cellular distribution of the neurotensin-hydrolysing neutral metalloendopeptidase 24.16 (EC 3.4.24.16) was examined by light and electron microscopic immunohistochemistry in adult rat mesencephalon. Light microscopic immunoradioautography revealed a ubiquitous distribution of the enzyme throughout the midbrain with a relative enrichment of grey matter areas including the substantia nigra, ventral tegmental area, interfascicular nucleus, interpeduncular nucleus, rostral and caudal linear rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
7
27
0
Order By: Relevance
“…Our previous electron microscopic study revealed the occurrence, within the midbrain tegmentum, of endocytic invaginations at the level of appositions between endopeptidase 3.4.24.16-immunoreactive neurons and astrocytes, suggesting a possible translocation of the enzyme between these two elements (Woulfe et al, 1992). This finding prompted us to investigate the possibility of a secretion of endopeptidase 3.4.24.16 by either astrocytes or neurons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous electron microscopic study revealed the occurrence, within the midbrain tegmentum, of endocytic invaginations at the level of appositions between endopeptidase 3.4.24.16-immunoreactive neurons and astrocytes, suggesting a possible translocation of the enzyme between these two elements (Woulfe et al, 1992). This finding prompted us to investigate the possibility of a secretion of endopeptidase 3.4.24.16 by either astrocytes or neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Whether these differences reflect complementary roles of the enzyme on peptide inactivation remains to be established. In this context, it is interesting to note that, at the level of neurotensinergic pathways, endopeptidase 3.4.24.16-immunopositive astrocytic elements are often directly apposed to endopeptidase 3.4.24.16-immunoreactive nerve cell bodies and/or dendrites (Woulfe et al, 1992). It is therefore tempting to speculate that although the endopeptidase 3.4.24.16 secreted form of astrocytes would act in the extracellular space, thereby restricting diffusion of released neurotensin, the neuronal membraneassociated activity would be responsible for the physiological inactivation of the peptide either in the synaptic cleft, beside neurotensin receptors, or inside early endosomal compartments in which receptor-ligand complexes would have been internalized (Mazella et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that neurotensin evoked a significant increase in extracellular GABA levels, which was comparable in magnitude to neurotensin-induced changes in GABA levels in subcortical sites. The small magnitude of neurotensinevoked GABA increases probably reflects metabolism of exogenously administered neurotensin by metalloendopeptidases (Woulfe et al, 1992), which play an important role in regulating neurotensin activity in vivo (Vincent et al, 1997a,b;O'Connor, 2001).…”
Section: Local Administration Of Neurotensin Increases Extracellular mentioning
confidence: 99%
“…BK is also efficiently cleaved in vitro by the closely related peptidases EP24.15 (also known as thimet oligopeptidase) and EP24.16 (also known as neurolysin) (21). We have recently shown that hypotensive responses to BK are markedly potentiated by the administration of a stable inhibitor of these enzymes N- [1- 16 has been localized to the plasma membrane in neurons, both in vivo (9,31) and in vitro (28), as well as in human kidney cells transfected with the peptidase (29). Given that neither enzyme possesses a transmembrane domain, the exact mechanism of association with the membrane is not understood.…”
mentioning
confidence: 99%